Childcraft Picture Atlas: A Book of Lands and Peoples - World Book, Inc. (UK World Book International, 1989)
1 atlas (288 p.) : col. ill., col. maps
"Also published under the title Children's illustrated atlas"--Verso added t.p.
Includes glossary and index.
Keywords: Encyclopedias (3GdehShYGJs; General; Children's atlases